Pengembangan Hutan Literasi Sekolah Berbasis Teknologi dalam Mendukung SDGs - Ridwan, Irwan Muhammad; Surahman, Endang; Susanti, Ernita; Sulistyaningsih, Dwi; Makiyah, Yanti Sofi; Maulidah, Rifa’atul; Sumantri, Agus (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2025)
21st-century education demands the development of literacy skills, technology utilization, and environmental awareness. One innovation that integrates these three aspects is the development of a School Literacy Forest, a nature-based learning space that integrates literacy activities and environmental education. SMP Islam Nurul Yaqin in Sodonghilir Sub-District, Tasikmalaya Regency has pioneered the "PENGHUNI SEKOLAH" program (School Literacy Forest Development) as a form of commitment to contextual learning. However, the utilization of this literacy forest area is still not optimal due to the lack of educational media, the absence of technology integration, and limited training for teachers and students. This community service activity aims to: Develop the school literacy forest into a technology-based learning space that supports cross-disciplinary learning; Enhance the capacity of teachers and students in utilizing information technology for the management and enrichment of environmental literacy content; Provide digital media such as interactive QR Codes, infographics, and e-literacy content; and Build a digital-based literacy documentation system accessible to the school community and the public. Implementation methods include teacher-student training and mentoring, creation of digital educational media (plant QR Codes, e-books, infographics), installation of temperature and humidity measuring instruments, and creation of a literacy forest location map. Based on the results of the partner response questionnaire distributed to teachers and students of SMP Islam Nurul Yaqin, this community service activity successfully achieved very positive results. Overall, respondents expressed high satisfaction with all the activities and products generated